2001
DOI: 10.1044/1092-4388(2001/054)
|View full text |Cite
|
Sign up to set email alerts
|

Early Phonetic and Lexical Development

Abstract: Researchers frequently examine the development of the single-word lexicon in the absence of phonetic data. Yet a large body of literature demonstrates relationships between the phonetics of babble and early speech, and it is clear that production skill is essential for establishing a lexicon. This study uses longitudinal productivity criteria to establish children's phonetic skill. Twenty children were followed from age 9 to 16 months, and their level of consistency of vocal patterns was examined in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
201
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(224 citation statements)
references
References 52 publications
16
201
1
6
Order By: Relevance
“…This is consistent with or higher than what has been reported for other large-sample studies of transcription reliability for consonants produced by prelinguistic infants (Davis & MacNeilage, 1995;McCune & Vihman, 2001). It might be expected, given the quality of the video and audio signal, that reliability would be higher than previously reported in the literature, but the nature of the study required rapid transcription to identify acquisition of VMS in as timely a way as possible.…”
Section: Production Data Collectionsupporting
confidence: 52%
See 2 more Smart Citations
“…This is consistent with or higher than what has been reported for other large-sample studies of transcription reliability for consonants produced by prelinguistic infants (Davis & MacNeilage, 1995;McCune & Vihman, 2001). It might be expected, given the quality of the video and audio signal, that reliability would be higher than previously reported in the literature, but the nature of the study required rapid transcription to identify acquisition of VMS in as timely a way as possible.…”
Section: Production Data Collectionsupporting
confidence: 52%
“…Two separate criteria were used to define the acquisition of a VMS. The first criterion, following McCune & Vihman (2001), was that a consonant be produced at least 10 times in each of three sessions, with no more than one session intervening with fewer than 10 occurrences. Second, since this study required a more dynamic approach to identifying VMS to permit timely perceptual testing, 50 occurrences of a consonant within one to three sessions was also accepted as evidence of a VMS.…”
Section: Production Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicit learning is facilitated when the child has developed a repertoire of phonological representations, as we noted earlier (McCune & Vihman, 2001;Storkel, 2001;Keren-Portnoy et al, 2005; cf. also Werker et al, 2002, who found a difference in the ability to notice a minimal phonological shift in nonsense word labels for novel objects as early as 14 months only in the case of children with a reported production vocabulary of over 25 words).…”
Section: The Sources Of Phonological Knowledgementioning
confidence: 75%
“…The beginnings of explicit word learning are accompanied by evidence of a "desire to know", as the child insistently points at different objects, for example, alternating pointing with turning to look at the adult interlocutor. The product of such learning is EXPLICIT LEXICAL RETRIEVAL, leading to spontaneous word use outside of a priming context (typically seen between the 4wp and the 25wp; this is "context-flexible" word use: McCune & Vihman, 2001). Figure 4 illustrates this advance in word learning, which underlies further advances in phonological knowledge.…”
Section: The Sources Of Phonological Knowledgementioning
confidence: 99%